Pengaruh Permainan Tradisional Panca Main Indonesia Terhadap Pemahaman Pancasila - Wardani, Trisna Kusuma; Gozi Andika Alvawaz; Akhmad Muzakkir (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This study aims to determine the effect of the traditional game Panca Main Indonesia on the understanding of Pancasila values among second-grade students at SDN 1 Dangiang. The research method employed was quantitative with a quasi-experimental design using a Nonequivalent Control Group Design. The sample consisted of 40 students, divided into an experimental class and a control class. The research instruments included multiple-choice tests, observations, and interviews. Data analysis was conducted through normality tests, homogeneity tests, t-tests, and descriptive analysis. The results indicate that the Panca Main Indonesia traditional game has a significant effect on students’ understanding of Pancasila values, as evidenced by a significance value < 0.05 and t-value > t-table. Descriptively, the average post-test scores of the experimental class were higher than those of the control class. Thus, the Panca Main Indonesia traditional game is proven to be effective in enhancing students’ comprehension of Pancasila values.